Prospects of measuring quantum entanglement in ττ final states at a future e+e− Higgs factory - Breuning Cedric; Bechtle Philip; Desch Klaus; Grefe Christian (EPJ Web of Conferences)
We introduce a method to study quantum entanglement at a future e+e− Higgs factory (here the Future Circular Collider colliding e+ and e− (FCC- ee) operating at √s = 240 GeV) in the ττ final state. This method is focused on the τ → πντ decay. We show how the introduced method works on simulated events without detector effects. When detector effects are applied, the necessary τ four-momenta can be reconstructed from kinematic constraints. We will discuss the advantages of e+e− collisions over pp collisions where the reconstruction of the ττ rest frame is more difficult. This discussion will focus on the influence of pT trigger cuts on the visible π± in the τ lepton decay.